The impact of European Union support programmes on the internationalisation of micro, small and medium-sized enterprises in the wine sector - Oliveira, Luís de (2019)
This dissertation has a twofold purpose: to get insight into the benefits to enterprises that come from internationalisation; and, to assess the impact of European Union (EU) internationalisation support programmes on wine sector micro, small and medium-sized enterprises (SMEs). To achieve this, a questionnaire was conducted to wine SMEs (42) which had access to internationalisation support programmes defined in the European Structural and Investment Funds 2014-2020, and an in-depth interview to a consultant to corroborate the findings. The results related to internationalisation strategies demonstrate that most of the companies have a positive experience with being active abroad earning the benefits identified by the literature: increased turnover, more stability, more innovation, among others. The truth is that most of the companies are conscious of the opportunities related with this type of strategy. However, at the same time, SMEs are also aware of the several challenges and their limitations. For instance, lack of adequate information regarding markets, lack of capital and the corporate business, like taxes and regulations, were the most identified ones. Difficulties that discourage most companies to increase or approach foreign markets. In this sense, public support can have a crucial role in assisting SMEs to engage in international strategies or develop them. The results have shown 9 out of 10 SMEs recognized that EU funds assisted them surpassing those barriers. The study gave valuable insight regarding the positive impact of public support, and at the same time possible improvements on how those supports can be more effective.